Perlindungan Hukum Terhadap Dosen Kontrak - Rakamas Pancasona; Dipo Wahjoeono (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the legal protection framework for contract lecturers in Indonesia by analyzing the structural inconsistencies between labor law regulations and higher education norms and their implementation within universities. Although Law No. 13 of 2003 as amended by Law No. 11 of 2020 and Government Regulation No. 35 of 2021 restrict fixed-term employment contracts (PKWT) to temporary work, universities continue to apply repeated contracts to lecturers whose duties are permanent and integral to the Tridharma of Higher Education. This practice creates legal uncertainty, particularly following Constitutional Court Decision No. 37/PUU-XXI/2023. Furthermore, despite statutory guarantees under Law No. 14 of 2005 and Law No. 12 of 2012, contract lecturers frequently experience discrimination in remuneration, social security, and career advancement. This study concludes that long-serving contract lecturers substantively qualify as permanent employees (PKWTT), necessitating status conversion to ensure justice, legal certainty, and constitutional compliance.